The effectiveness of the Total Physical Response (TPR) method on Arabic vocabulary comprehension for students with special needs at Hayat Islamic Primary School Malang - Ferolisa, Ardhea Fero; amrullah, Abdul Malik karim; Kholil, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to examine the effectiveness of the Total Physical Response (TPR) method in improving Arabic vocabulary acquisition among students with special needs at MI Hayatul Islamiyah Malang. Using a quantitative method with a one-group experimental design (pre-test and post-test), this study measured changes in vocabulary acquisition before and after the implementation of TPR. The results showed a significant increase in students' vocabulary scores after the implementation of the TPR method. The p-value of 0.00 is smaller than 0.05, so Ha can be accepted and H0 is rejected. This shows that there is a significant increase in students' comprehension after the implementation of the TPR method. Before the treatment, the mean score of the students' pre-test was 55, and after the treatment, the mean score of the post-test increased to 83.75. This shows that the TPR method is effective in improving students' vocabulary comprehension, so that their ability to understand new vocabulary increases significantly. This study concludes that the TPR method is effective in improving Arabic vocabulary acquisition, which has the potential to support the academic and social development of students with special needs, and emphasizes the importance of an inclusive and student-centered approach to education.